2022
DOI: 10.1002/ppul.26107
|View full text |Cite
|
Sign up to set email alerts
|

What caregivers believe affected the quality of implementation of asthma‐related family management models (AFMM) during COVID‐19: A phenomenological qualitative study

Abstract: Purpose The recurrent COVID‐19 epidemic in China has disrupted many aspects of daily life for children with asthma and their caregivers, while negatively impacting their asthma family management models (AFMM). This phenomenological qualitative study identifies what affects the quality of implementation of AFMM in this population and outlines potential coping strategies for the caregivers. Methods We used purposive sampling to conduct semistructured interviews with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However of studies focusing on children, negative psychosocial outcomes (eg, anxiety, depression) have been reported among children with asthma 4 and their parents. 5 , 6 In a qualitative study, parents reported fear about their child contracting COVID-19, challenges in the family such as managing family dynamics and child care concerns during the pandemic, and service delivery changes such as increased reliance on virtual care. 6 Parents drew on an array of supports including informal support (eg, friends and family) formal support (eg, parent support groups), and financial resources (eg, government programs offering financial benefits) to cope with these changes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However of studies focusing on children, negative psychosocial outcomes (eg, anxiety, depression) have been reported among children with asthma 4 and their parents. 5 , 6 In a qualitative study, parents reported fear about their child contracting COVID-19, challenges in the family such as managing family dynamics and child care concerns during the pandemic, and service delivery changes such as increased reliance on virtual care. 6 Parents drew on an array of supports including informal support (eg, friends and family) formal support (eg, parent support groups), and financial resources (eg, government programs offering financial benefits) to cope with these changes.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Parents drew on an array of supports including informal support (eg, friends and family) formal support (eg, parent support groups), and financial resources (eg, government programs offering financial benefits) to cope with these changes. 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations